Identification of Colletotrichum spaethianum causing sugar beet leaf spot in North Dakota, USA - M.Z.R. Bhuiyan Ziaur; Dilip Kumar Lakshman; Adnan Ismaiel; Prashanta Bhui; Mohamed Khan (Journal of Plant Protection Research, 2025)
Sugar beet leaves with dark brown to blackish, necrotic lesions were found in a grower’s field in Casselton, North Dakota, USA in August 2021. Morphological features of the isolates obtained in growth media from the diseased samples were observed and documented. The pathogenicity of the randomly selected isolates developed identical disease symptoms on the inoculated leaves. Molecular characterization of the isolates was conducted by identifying homologies with sequences of the internal transcribed spacer, the largest subunit of RNA polymerase II (rpb2), β-tubulin (β-tub), calmodulin (CaM), and plasma membrane ATPase (Pma1) genes followed by multilocus phylogenic analyses. Based on morphological characteristics, pathogenicity, and molecular analyses, the causal organism was identified as Colletotrichum spaethianum. This is the first report of C. spaethianum causing leaf spot on sugar beet in North Dakota, USA. The report will help growers design an effective disease management for a novel pathogen in sugar beet in the Red River Valley of Minnesota and North Dakota, USA.